Hands-on CRISPR/Cas9 genome editing workshop / Dr Fazleen Haslinda Mohd Hatta - Mohd Hatta, Fazleen Haslinda (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy UiTM Puncak Alam hosted a two-day workshop on CRISPR/Cas9 genome editing from 12th to 13th of July 2023. The workshop aimed to provide participants with theoretical and practical knowledge on the principles and applications of CRISPR/Cas9 technology. Dr. Fazleen Hatta, Mr. Ahmad Azani, and Mrs. Ruhil Nadirah Che Omar, scientists who are actively working in the field of genome editing, led the workshop. The workshop consisted of lectures, demonstrations, and hands-on sessions covering various aspects of CRISPR/Cas9 genome editing, such as ethics and biosafety, guide RNA design, vector cloning, cell sorting, transfection efficiency, genome editing confirmation, and troubleshooting. The workshop also provided opportunities for participants to interact with the speakers and facilitators, pose questions, and share their experiences. A total of seven participants attended the workshop, representing different disciplines and institutions.